THE VISUAL SECRET SHARING SCHEME BASED ON THE RGB COLOR SYSTEM - Eric Christiandi Sulaiman; Mariskha Tri Adithia (JUTI: Jurnal Ilmiah Teknologi Informasi, 2017)
The visual secret sharing (VSS) scheme is a method to maintain the confidentiality of a se-cret image by sharing it to some number participants. A (k, n) VSS divides the secret images into n parts, that are called shadows ; to recover the secret back, k shadows should be stacked. Some methods have been developed to implement VSS for color images. However, the methods are only suitable for images with limited number of colors. When more colors are used, the resulted stacked shadow image becomes unclear. Besides that, the size of the shadows becomes bigger as more colors are used. We develop a new method implementing the VSS using the RGB color system. Using our method, the problem related to the unclear stacked shadow image can be overcome.